Pesantren and the Human Development Index in Indonesia Post Law Number 18 of 2019 - M Faishal Khoirurrijal; Abdul Rahim Karim; Achmad Zaini; Mohamad Salik (The Institute of Research and Service Community IPMAFA Pati, 2023)
This research intends to determine the extent to which the potential of pesantren is based on the mandate contained in Law no. 18 in 2019 about Pesantren in an effort to increase the Human Development Index (IPM) in Indonesia. This research is qualitative research using a literature study approach in the data collection process, both primary and secondary. The primary data in the form of the Pesantren Law was then analyzed in terms of the Human Development Index indicators with the assistance of several secondary sources such as journal articles, web articles, and books. The results of this research indicate that Pesantren has the potential in efforts to increase the Human Development Index (HDI) in Indonesia through two dimensions: 1) Pesantren have the potential to increase the Knowledge dimension (Expected School Length and Average School Length) in its function as an educational institution through the provision of formal education Pesantrens in the form of the Satuan Pendidikan Muadalah (SPM), Pendidikan Diniyah Formal (PDF), and Ma'had Aly; 2) Pesantren have the potential to increase the dimension of a Decent Standard of Living through their function in community empowerment with various training programs and economic empowerment and entrepreneurship.